To solve the equation \(1.26(x - 7.352) = 6.426\), follow these steps:
-
Distribute \(1.26\) on the left-hand side: \[ 1.26x - 1.26 \times 7.352 = 6.426 \] Calculate \(1.26 \times 7.352\): \[ 1.26 \times 7.352 \approx 9.25632 \] So the equation becomes: \[ 1.26x - 9.25632 = 6.426 \]
-
Add \(9.25632\) to both sides: \[ 1.26x = 6.426 + 9.25632 \] Calculate \(6.426 + 9.25632\): \[ 6.426 + 9.25632 \approx 15.68232 \] Now the equation is: \[ 1.26x = 15.68232 \]
-
Divide both sides by \(1.26\): \[ x = \frac{15.68232}{1.26} \] Calculating it gives: \[ x \approx 12.452 \]
Thus, the solution to the equation is: \[ \boxed{12.452} \]